Power Start-Up of the IVG.1M Reactor with Low-Enriched Uranium Fuel: Main Results - Erlan Batyrbekov; Vladimir Vityuk; Viktor Baklanov; Vyacheslav Gnyrya; Almas Azimkhanov; Radmila Sabitova; Irina Prozorova; Yuriy Popov; Ruslan Irkimbekov; Yekaterina Martynenko (Energies)
In support of global efforts to strengthen the nuclear non-proliferation regime, the IVG.1M research water-cooled thermal reactor at the National Nuclear Center of the Republic of Kazakhstan was successfully converted to low-enriched uranium (LEU, 19.75% 235U) fuel in 2023. The reactor’s operability with innovative bimetallic, fiber-type, dual-blade LEU fuel rods was experimentally verified during power start-up experiments. The test program included investigations of power distribution in the core, evaluation of temperature, power, and hydrodynamic reactivity effects, and the measurement of fission product release to the coolant. The results were in good agreement with safety calculations, confirming that the enrichment reduction did not degrade reactor performance characteristics. It was shown that the power reactivity effect increased by more than 1.5 times at a power level of 9 MW. The measured temperature reactivity coefficient (≈0.021 βeff/°C) and the level of fission product release remained within acceptable and expected limits.